2017
DOI: 10.3329/bjp.v12i1.29940
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of daclatasvir plus peginterferon alfa and ribavirin for patients with chronic hepatitis C genotype 4 infection

Abstract: Clinical trials evaluating the safety and efficacy of daclatasvir for chronic hepatitis C virus (HCV) genotype 4 infection are scarce and yet with small sample sizes. Therefore, we conducted this systematic review to investigate the efficacy of daclatasvir in HCV genotype 4 treatment. A computer literature search of PubMed, Scopus, Embase, Ovid, Web of knowledge, and Cochrane central was conducted. We selected studies comparing daclatasvir plus peginterferon-alfa/ribavirin versus placebo plus peginterferon-alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The authors reported that the regimen achieved 99% SVR in patients with chronic genotype 4 infection [12]. Similarly, daclatasvir containing regimen achieved 95% SVR in patients with genotype 4 infection [13].…”
Section: Discussionmentioning
confidence: 97%
“…The authors reported that the regimen achieved 99% SVR in patients with chronic genotype 4 infection [12]. Similarly, daclatasvir containing regimen achieved 95% SVR in patients with genotype 4 infection [13].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, HCV infection is still significant public health and economic concern in many parts of the world. HCV infection affects more than 130 million people worldwide, with nearly half a million people dying each year from HCV-related liver diseases as it is not easy to treat so far [2][3][4][5][6]. According to the last five years' data record collected by the ministry of health of the Kingdom of Saudi Arabia (KSA), there is a notable increase in the incidence rate of hepatitis C in the kingdom (Incidence rate/100000 population: 5.48 to 10.27) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic analysis of HCV isolates from various parts of the world demonstrated six major hepatitis C virus (HCV) genotypes, known as types1-6, as well as various subtypes [12], and a newly discovered seventh type (Innogenetic). Variants isolate obtained predominantly in Southeast Asia were discovered to differ among types and subtypes [13,14]. They were integrated into their nearest phylogenetic type (all type 6, except one type 3 strain).…”
Section: Introductionmentioning
confidence: 99%